On a Question of Erdős and Gimbel on the Cochromatic Number - Heckel, Annika (The Electronic Journal of Combinatorics, 2024)
In this note, we show that the difference between the chromatic and the cochromatic number of the random graph G_n,1/2 is not whp bounded by n^1/2-o(1), addressing a question of Erdős and Gimbel.